Punitive school discipline as a mechanism of structural marginalization with implications for health inequity: A systematic review of quantitative studies in the health and social sciences literature. Issue 1 (17th November 2022) - Duarte, Catherine dP.; Moses, Candice; Brown, Melissa; Kajeepeta, Sandhya; Prins, Seth J.; Scott, Janelle; Mujahid, Mahasin S.
Abstract: Punitive school discipline deploys surveillance, exclusion, and corporal punishment to deter or account for perceived student misbehavior. Yet, education and legal scholarship suggests it fails to achieve stated goals and exacerbates harm. Furthermore, it is disproportionately imposed upon Black, Latinx, Native/Indigenous, LGBTQIA, and disabled students, concentrating its harms among marginalized young people. Its implications for health, however, are less clear. Using public health theories of sociostructural embodiment, we propose a framework characterizing pathways linking societal ideologies (e.g., racism) to punitive discipline with implications for health and health inequity and then present our systematic review of the punitive school discipline–health literature ( N = 19 studies) conducted in accordance with PRISMA guidelines. Data were extracted on guiding theories, study characteristics, measurement, methods, and findings. This literature links punitive school discipline to greater risk for numerous health outcomes, including persistent depressive symptoms, depression, drug use disorder in adulthood, borderline personality disorder, antisocial behavior, death by suicide, injuries, trichomoniasis, pregnancy in adolescence, tobacco use, and smoking, with documented implications for racial health inequity. Using our adapted framework, we contextualize results and recommend avenues for future research. Our findings support demands to move away from punitive school discipline toward health‐affirming interventions to promote school connectedness, safety, and wellbeing. Abstract : Punitive school discipline deploys surveillance, exclusion, and corporal punishment to deter perceived student misbehavior; however, research suggests it is ineffective, exacerbates harm, and disproportionately targets marginalized young people. Based on existing theory and findings from a systematic review of the literature, we propose a framework characterizing pathways linking societal ideologies (e.g., racism) to punitive discipline with implications for adverse population health outcomes and racial health inequity. Findings support moving away from punitive school discipline towards health‐affirming interventions.